Performance Analysis of The Effect on Insertion Guide Vanes For Rectangular Elbow 900 Cross Section - Nugroho, Setyo; Hidayatulloh, Achmad Arifudin (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
The use of elbow or curved pipe in the installation of piping has a loss of pressure (pressure drop) which could lead the power of pump that drive the fluid and decrease the energy efficiency of the system. The pressure drop is caused by the curved shape of the elbow that cause pressure on the outer wall (outter) larger and blocking off the pace of the fluid, and flow pressure losses caused by friction, flow separation and secondary flow. A method that can be used to reduce flow separation and pressure loss in the elbow is by the insertion guide vane. The test model in the form of rectangular elbow 900Â with a radius ratio (rc/Dh) = 1.1249 without using a guide vane and number of guide vane insertion one until three guide vanes. With Reynolds number ReDh â 8.6 Ã 104. The velocity inlet is uniform, the measured variable is static pressure. Static pressure was measured using an inclined manometer. With variation the number of guide vane gives a more effect on the value of pressure drop, the largest pressure drop until 123.35% compared to that without guide vane. The velocity distribution profile on the outlet side becomes more uniform. The magnitude of this pressure drop occurs as a result of the increased flow friction and its secondary flow become smaller.